Statistical study of Ionospheric Conductivity Dependence of the Subauroral Polarization Streams using the SuperDARN Hokkaido East HF Radar - Zhang, Yuting; Nishitani, Nozomu; Hori, Tomoaki (2018)
The Ninth Symposium on Polar Science/Ordinary sessions: [OS] Space and upper-atmosphere sciences, Wed. 5 Dec. / Entrance Hall (1st floor), National Institute of Polar Research conference object